Replication-competent foamy virus vaccine vectors as novel epitope scaffolds for immunotherapy - Lei, Janet; Osen, Wolfram; Gardyan, Adriane; Hotz-Wagenblatt, Agnes; Wei, Guochao; Gissmann, Lutz; Eichmüller, Stefan B.; Löchelt, Martin (PLOS ONE, 2015)
The use of whole viruses as antigen scaffolds is a recent development in vaccination that improves immunogenicity without the need for additional adjuvants. Previous studies highlighted the potential of foamy viruses (FVs) in prophylactic vaccination and gene therapy. Replication-competent FVs can trigger immune signaling and integrate into the host genome, resulting in persistent antigen expression and a robust immune response. Here, we explored feline foamy virus (FFV) proteins as scaffolds for therapeutic B and T cell epitope delivery in vitro. Infection- and cancer-related B and T cell epitopes were grafted into FFV Gag, Env, or Bet by residue replacement, either at sites of high local sequence homology between the epitope and the host protein or in regions known to tolerate sequence alterations. Modified proviruses were evaluated in vitro for protein steady state levels, particle release, and virus titer in permissive cells. Modification of Gag and Env was mostly detrimental to their function. As anticipated, modification of Bet had no impact on virion release and affected virus titers of only some recombinants. Further evaluation of Bet as an epitope carrier was performed using T cell epitopes from the model antigen chicken ovalbumin (OVA), human tyrosinase-related protein 2 (TRP-2), and oncoprotein E7 of human papillomavirus type 16 (HPV16E7). Transfection of murine cells with constructs encoding Bet-epitope chimeric proteins led to efficient MHC-I-restricted epitope presentation as confirmed by interferon-gamma enzyme-linked immunospot assays using epitope-specific cytotoxic T lymphocyte (CTL) lines. FFV infection-mediated transduction of cells with epitope-carrying Bet also induced T-cell responses, albeit with reduced efficacy, in a process independent from the presence of free peptides. We show that primate FV Bet is also a promising T cell epitope carrier for clinical translation. The data demonstrate the utility of replication-competent and -attenuated FVs as antigen carriers in immunotherapy.
Gesehen am 19.11.2018